TEACHER EDUCATION STUDENTS’ SELF-ASSESSMENT OF COMPETENCE FOR COOPERATION WITH PARENTS - Đuranović, Marina; Opić, Siniša; Klasnić, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
To be a teacher in the times of today is a great challenge. In order to respond to the needs of modern society, lifelong learning and mastery of numerous competences are expected of the teacher in various fields of work, wherein cooperation with parents is one of the extremely important areas. The goal of the research was to gain insight into self-assessment of competence of students at the Faculty of Teachers Education for future cooperation with parents. The research was implemented during October, 2020, on the sample of 416 students in their first, third and fifth year at the Faculty of Teacher Education of the University of Zagreb (Croatia). It is a futurological research for whose needs a questionnaire was designed with 26 manifest variables on an ordinal, five-degree Likert-type scale. From the manifest set of variables of competence for future cooperation with parents, three composite variables were formed: general cooperation competence, competence for cooperation directed to teaching efficacy, and competence for cooperation directed to communication with parents. The results show that the total student self-assessment of competences for future cooperation with parents is relatively positive, and the existence of statistically significant differences in all three composite variables. Faculties educating future teachers should introduce obligatory courses which would sensitise and capacitate them for future cooperation with parents.